The First Saints of Hungary and Nemanjić Serbia: The Model of the Holy Trinity - Piperski, Nikola P. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines the possibility that the first “national” saints in Nemanjić Serbia and medieval Hungary were conceived in triads, resembling the image of the Holy Trinity or the triune God. During the Middle Ages, for peoples without direct representatives in Christian history, “national” saints—whether individuals or groups—were shaped according to selected models, often drawn from early Christian times and biblical history. Archetypal images from the Christian tradition show that their selection always carried political significance, reflecting an ongoing tension between the past and the present. It is important to explore the potential political message behind the proposed model of the Holy Trinity. This exploration should take into account the political and historical context during the establishment of the earliest saintly and dynastic cults in early Christian Hungary under the Árpád dynasty, as well as in Serbia during the era of the first Nemanjićs. Since both states, after their foundation, were confronted with the challenge of establishing and consolidating stable royal, dynastic, and ecclesiastical authority, along with the need to unify it, the question arises if the saintly triads of the Nemanjićs and the Árpáds, crafted in the image of the Holy Trinity, could have served as a fitting framework for developing political, dynastic, and ecclesiastical rhetoric aimed at conveying the notion of their unity and legitimacy, based on their divine selection and ordination status. Ultimately, one must consider how closely related these two proposed models were and whether, and to what extent, the older Hungarian model may have influenced the Serbian model, which is over a century newer.